Uso de Dinoprost Trometamina nas coletas de sêmen e seu efeito na qualidade do ejaculado - Amaral, Luciano Bianco do (2025)
With the advancement of global swine production, reproductive biotechnologies have played an increasingly relevant role, contributing to the improvement of zootechnical outcomes in high-performance animals. Swine semen collection and processing centers have significantly evolved regarding infrastructure, equipment, and quality control of the doses delivered to producers. Stricter protocols for bacterial contamination control and the use of advanced collection techniques have ensured higher quality semen samples for laboratory evaluation and processing. Furthermore, the genetics of the breeders also exert a determining influence, since different lineages present characteristics that directly impact semen production and quality. This study aimed to evaluate the use of dinoprost tromethamine in the form of collection, the genetic lineage, and the interval between collections on swine semen quality parameters, including volume, concentration, and sperm motility. Three hundred and fifty-five breeders (N = 653) from four genetics company lineages (Large White, Duroc, Landrace and hybrid) were evaluated, totaling 22,977 collections carried out over 12 months at a swine semen collection and processing center. Statistical analyses included factorial ANOVA, Tukey’s test (P < 0.05), and regression analysis. Results indicated that automatic collection provided higher volume and sperm motility, while concentration was higher in manual collections. The use of dinoprost increased motility in animals of the Hybrids lineage and raised overall concentration, although it reduced the ejaculated volume. Sperm concentration also increased with longer intervals between collections (P < 0.05). The collection method, use of dinoprost, genetic lineage, and interval between collections significantly influence seminal quality in swine.